2017
DOI: 10.3390/bs7040071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Self-Rated Health and Lifestyle and Food Habits in Japanese High School Students

Abstract: Self-rated health (SRH), a subjective assessment of health status, is extensively used in the field of public health. It is an important and valid measure that is strongly related to morbidity, mortality, longevity and health status. Adolescence is a crucial period for the formation of health status, because health-risk behaviours (e.g., skipping breakfast) are often established during this period. In this study, we investigated the relationship of SRH with lifestyle and eating habits in Japanese high school s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
5
16
0
Order By: Relevance
“…These findings suggest that SRH is a key factor affecting junior high school students' health. These data were similar to the findings of our previous study on high school students, which described five items related to miscellaneous health issues that displayed a significant relationship with SRH (Osera et al, 2017). High SRH was significantly associated with not being irritated and not suffering with headaches (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These findings suggest that SRH is a key factor affecting junior high school students' health. These data were similar to the findings of our previous study on high school students, which described five items related to miscellaneous health issues that displayed a significant relationship with SRH (Osera et al, 2017). High SRH was significantly associated with not being irritated and not suffering with headaches (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
“…Some researchers have suggested that these observations indicate that morning habits are associated with the health status of adolescents (Sjoberg et al, 2003). Our previous study indicated that morning habits are a very important factor affecting high school students' SRH (Osera et al, 2017). The current study suggests that students who have good sleeping habits (i.e.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations